HUBUNGAN EFIKASI DIRI DAN KEPATUHAN PADA PASIEN HIPERTENSI DI RSUD KARAWANG - Arfania, Maya; Nuraeni, Eni; Frianto, Dedy; Amal, Andi Nurzakiah; Fatmala, Widya; Nurhapit, Evi Riszka; Alfarizzy, Ali (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Medication adherence can affect patient health, one of the factors that can influence medication adherence in patients is self-efficacy. Self-efficacy has a positive relationship, so it is very important for hypertensive patients to maintain their treatment. Self-efficacy is very important for hypertensive patients during their treatment because it has a positive relationship. This study aims to determine how the influence of self-efficacy on medication adherence in hypertensive patients at Karawang Regional Hospital using a cross-sectional method based on a questionnaire (Medication Adherence Rating Scale). The questionnaire data (Medication Adherence Rating Scale) medication adherence and self-efficacy were analyzed using the chi-square test method which can determine the influence and relationship between medication adherence and self-efficacy. Based on the research that has been done, self-efficacy in hypertensive patients at Karawang Regional Hospital with a good self-efficacy level of 72.8%, with compliant compliance of 63.7% and non-compliant patients of 36.3%. There is no significant relationship between self-efficacy and adherence in hypertensive patients at Karawang Regional Hospital.